Effectiveness of Anti-Lice Shampoo from Lemongrass Stalk (Cymbopogon Citratus) - Sjamsiah, Sjamsiah; Nurwahyuni, Nurwahyuni; Gani, Rahmiani (EduChemia: Jurnal Kimia dan Pendidikan, 2025)
Head lice (Pediculus humanus capitis) are ectoparasites that attack the human head, causing excessive itching. To overcome this problem, shampoo with active substances from natural sources can be used, namely, kitchen lemongrass (Cymbopogon citratus). This study was designed to determine the effects of various concentrations of lemongrass stalk extract and the optimal concentration of the anti-head lice shampoo on head louse mortality. The results of the phytochemical screening revealed that the lemongrass stalk extract contains flavonoids, tannins, terpenoids, saponins and alkaloids. Lemongrass stalk extract can be used as a shampoo formulation with several concentrations ranging from 3%, 5%, 7% and 9%. The characteristic results revealed a thick liquid, homogeneous, brown to blackish brown color, a characteristic smell of the lemongrass stalk, a foam height range of approximately 6–5 cm, a pH range of approximately 5–6, and a viscosity range of approximately 100–5700 cP. The optimum concentrations that can kill head lice effectively and meet the SNI requirements for an adequate and safe shampoo to use are shampoo at concentrations of 5% and 7%.